Flow Asymmetric Propargylation: Development of Continuous Processes for the Preparation of a Chiral β‐Amino Alcohol. Issue 32 (7th July 2017) - Li, Hui; Sheeran, Jillian W.; Clausen, Andrew M.; Fang, Yuan‐Qing; Bio, Matthew M.; Bader, Scott
Abstract: The development of a flow chemistry process for asymmetric propargylation using allene gas as a reagent is reported. The connected continuous process of allene dissolution, lithiation, Li‐Zn transmetallation, and asymmetric propargylation provides homopropargyl β‐amino alcohol1 with high regio‐ and diastereoselectivity in high yield. This flow process enables practical use of an unstable allenyllithium intermediate. The process uses the commercially available and recyclable (1 S, 2 R )‐ N ‐pyrrolidinyl norephedrine as a ligand to promote the highly diastereoselective (32:1) propargylation. Judicious selection of mixers based on the chemistry requirement and real‐time monitoring of the process using process analytical technology (PAT) enabled stable and scalable flow chemistry runs. Abstract : Go with the flow : Continuous flow is used for the practical preparation of highly reactive allenyllithium from allene gas under non‐cryogenic conditions. On‐line process analytical technologies such as FlowIR allowed real‐time monitoring of the formation of reactive intermediates.